Determination of Total Phenolic and Flavonoid Content, Antidiabetic, and Antioxidant Activities of Leaves and Seeds Extracts of Eucalyptus robusta Sm. and Ageratina adenophora Spreng - Regmi, Sarala; Sharma, Khaga Raj (Journal of Nepal Chemical Society, 2023)
The present study aimed at the determination of total phenolic and flavonoid content and biological activities of Eucalyptus robusta (Sm.) and Ageratina adenophora (Spreng.) growing in Kathmandu Nepal. People have been using these medicinal plants for many years against infectious diseases and to control diabetes. The extraction of plant secondary metabolites was done by the cold percolation method. The total phenolic (TPC) and flavonoid content (TFC) were quantified by the Folin-Ciocalteu phenol reagent and aluminium chloride colorimetric method. The α-amylase enzyme inhibition activity was performed to evaluate the antidiabetic property of plant extracts. The antioxidant potential of plant extracts was evaluated by DPPH (2,2-diphenyl- 1-picrylhydrazyl) radical scavenging assay. The methanol extract of Ageratina adenophora Spreng leaves is found rich in plant secondary metabolites of a yield percentage 36.83% whereas Eucalyptus robusta Sm. leaves and seeds have a yield percentage of 30.75% and 27.12% respectively. The extract of E. robusta leaves showed the highest phenolic content (200.89±6.67 mg gallic acid equivalent/g of dry extract) and A. adenophora Spreng. leaves extract showed the flavonoid content (0.49±0.02 mg quercetin equivalent/g of dry extract) among the three samples studied, respectively. The extract of E. robusta Sm. seeds showed the strongest DPPH radical scavenging activity with a half-maximal inhibitory concentration IC50 of 110.8±1.73 μg/mL. The extract of A. adenophora Spreng. was found potent towards α-amylase enzyme inhibition activity of IC50 16.05±0.24 μg/mL whereas E. robusta Sm. leaves and seeds extracts showed IC50 21.93±1.24 mg/mL and 21.82±0.09 mg/mL respectively. This study showed the leaves and seeds extracts of these two medicinal plants are found rich in phenolic and flavonoid compounds. These medicinal plants could be used to isolate the natural antioxidant and antidiabetic compounds that may be potential drug candidates in the future drug discovery process. This study supports providing scientific validation for using these medicinal plants against diabetes.